The implication of violation of cooperative principle in discourse on corruption of Indonesia Lawyers Club - Mangatur Sinaga; Dahnilsyah Dahnilsyah (Journal of Educational Sciences, 2018)
This article discusses the violation implicature of cooperative principle of discourse on corruption of Indonesia Lawyers Club. The applied theories are: (1) Searle’s speech acts (1969); (2) Austin’s Locutionary, Illocutionary, and Perlocutionary (1962); (3) Grice’s conversational implicatures and cooperative principles (in Leech,1993); (4) Levinson’s pragmatics and semantic deviation  (1983), Parker’s pragmatics (in Rahardi, 2005;48); (5) Spencer and Wilson’s relevance theory (in Rahardi, 2010). Data were gathered by means of listening and recording. The speeches were analyzed by employing the maxim violation and implicatures theories. The violation of cooperative principle implies (1) the speakers fully comprehend the speech, (2) Government has insufficient budget to pay the judges of regional anti-corruption court, (3) Government seems skeptical about the regional judge selection test, (4) The speakers are fully confident that they posses capability of eradicating corruption, (5) Both payment and allowance of the regional judge of anti-corruption court do not receive scholarly attention that have made difficult for them to work as  law enforcers and as justice enforcers, (6) Some negative effects emerged by virtue of the poor planning of the establishment of the regional court, (7) The anti-corruption court lost dignity; The role of Judicial commission is not effective in providing guidances to the judges, (9) All elements have committed corruption like termites keep encircling nation, (10) issues on corruption are not seriously discussed (11) regional elections indirectly trigger corruption.